Species‐specific PCR assays for Gambierdiscus excentricus and Gambierdiscus silvae (Gonyaulacales, Dinophyceae). Issue 3 (21st June 2019) - Litaker, R. Wayne; Tester, Patricia A.; Vandersea, Mark W.
Abstract : The two most toxic Gambierdiscus species identified from the Caribbean are G. excentricus and G. silvae . These species are the primary causes of ciguatera fish poisoning and likely contribute disproportionately to the toxicity of marine food webs. While Gambierdiscus species are difficult to distinguish using light or scanning electron microscopy, reliable species‐specific molecular identification methods have been developed and used successfully to identify a number of other Gambierdiscus species. Corresponding species‐specific assays are not yet available for G. excentricus and G. silvae, which imposes limitations on species identification and related ecological studies. The following note describes species‐specific polymerase chain reaction assays for G. excentricus and G. silvae that can be used for these purposes.